2023
DOI: 10.1038/s41598-023-31228-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder (PTSD) probability among parents who live in Kandahar, Afghanistan and lost at least a child to armed conflict

Abstract: The last 4 decades of conflict in Afghanistan resulted in incalculable deaths, injuries, and millions of displacements. Although there are routine reports on casualties of the warfare, the information on its long-term psycho-social sequelae is somehow discounted. This study aimed to assess post-traumatic stress disorder (PTSD) probability and its associated factors among parents who live in Kandahar, the southern province of Afghanistan, and lost at least one child to armed conflict. We conducted a health-faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The ongoing multidimensional conflict in Afghanistan and its inevitable psycho-social and economic consequences have undoubtedly contributed to the psychological problems of Afghans. 40 , 41 The findings of this study portray a high prevalence (51.8%) of depressive symptoms in our study participants. Previous studies have shown that depression is common in patients with uncontrolled hypertension and may interfere with blood pressure control.…”
Section: Discussionsupporting
confidence: 50%
“…The ongoing multidimensional conflict in Afghanistan and its inevitable psycho-social and economic consequences have undoubtedly contributed to the psychological problems of Afghans. 40 , 41 The findings of this study portray a high prevalence (51.8%) of depressive symptoms in our study participants. Previous studies have shown that depression is common in patients with uncontrolled hypertension and may interfere with blood pressure control.…”
Section: Discussionsupporting
confidence: 50%
“…At the same time, a prevalence estimate based on cut-off values rather than on clinical interviews is common in studies in crisis areas (cf. Ahmadi et al., 2022 ; Kovess-Masfety et al., 2021 ; Rahimi et al., 2023 ). Second, a generalization of the results to age or social groups other than university students is not possible, as the study focused only on this highly educated group.…”
Section: Discussionmentioning
confidence: 99%
“…An even greater mental load was reported by Cardozo et al. (2004) based on a national multistage, cluster, population- based mental health survey conducted in 2002: Using established cut-off scores, 67.7% of the participants suffered from significant depression and 42.1% from posttraumatic stress (see also Kurt et al., 2022 ; Neyazi et al., 2023a ; Panter-Brick et al., 2009 ; Rahimi et al., 2023 ; Scholte et al., 2004 ). High rates of mental disorders were also reported in the immediate aftermath of the Taliban take-over: In a sample of adolescents recruited from high schools in Kabul between November and December 2021, half of participants met criteria for probable posttraumatic stress disorder (PTSD, 51.6%) and depression (48.9%; Ahmadi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“…1 Factors that immensely increase vulnerability, such as poverty, unemployment, and illiteracy, are prevalent in Afghanistan. 14,15 In light of the underreporting of mental health conditions, the authentic and multidimensional burden of the conflict remains unknown. 15 The latter enigma underscores the urgency to enhance mental health research that may provide insights into humanitarian assistance and the development of evidence-based bio-psycho-social interventions.…”
Section: Opportunities For Health Researchmentioning
confidence: 99%